Enhancing social and health care educators’ competence in digital pedagogy: A pilot study of educational intervention - Ryhtä Iina; Elonen Imane; Hiekko Mari; Katajisto Jouko; Saaranen Terhi; Sormunen Marjorita; Mikkonen Kristina; Kääriäinen Maria; Sjögren Tuulikki; Korpi Hilkka; Salminen Leena (Finnish Social and Health Informatics Association (FinnSHIA), 2025)
The purpose of this pilot study was to explore connection of an educational intervention on the competence of health care educators and educator candidates (n=11) in digital pedagogy as a part of national TerOpe project. An educational intervention, Basics of Digital Pedagogy was developed by the TerOpe project’s experts. The participating educators and educator candidates of the educational intervention were recruited from the universities and university of applied sciences, which were involved in TerOpe project. All the participants of the educational interventions were invited to take part in this study. The educational intervention was conducted during spring 2019. Pre- and post-tests were implemented digitally by using an Educators’ and Educator Candidates’ Competence in Digital Pedagogy self-assessment instrument (OODI), which was developed for this study. The OODI includes 32 items divided in six digital competence areas professional engagement, digital resources, teaching and learning, assessment, empowering learners and facilitating learners’ digital competence. The data was analysed statistically. The self-assessed level of overall competence in digital pedagogy and competence in all competence areas of digital pedagogy increased statistically significantly during the intervention. The educational intervention used in this study seems to increase educators’ self-assessed competence in digital pedagogy. We recommend that all educators be encouraged to conduct continuous education on the basics of digital pedagogy.